Analisis Sentimen Crawling Data dari Sosial Media X tentang Gaza Menggunakan Metode SVM dan Decision Tree - Jhosefhin, Nicola Van Robert; Dewi, Christine (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
The Palestinian conflict with Israel has attracted a lot of attention from the world, especially in the Gaza Strip after the Hamas group took over the leadership, so that people often make tweets (posts) with various views, some have neutral, positive, negative views. Sentiment analysis is used to analyze data obtained from posts on Twitter. The purpose of this study is to determine the public's views on the Gaza Strip by applying the Decision Tree and Support Vector Machine algorithms to measure their level of accuracy. The results of the sentiment analysis show 805 neutral data, 415 positive, and 308 negative, then the Support Vector Machine algorithm produces the highest level of accuracy with a value of 73.86 which can be categorized as good.